Lack of association between LRRK2 G2385R and cognitive dysfunction in Korean patients with Parkinson's disease. (February 2017) - Hong, Jeong Hoon; Kim, Yue Kyung; Park, Jae Seol; Lee, Ji Eun; Oh, Mi Sun; Chung, Eun Joo; Kim, Jeong-Yeon; Sung, Young-Hee; Lyoo, Chul Hyoung; Lee, Jae Hyeok; Kwon, Do-Young; Kim, Hyun Sook; et al.
Highlights: Longer PD duration, older age-at-study entry and presence of depression were associated with cognitive dysfunction in PD. Heterozygous carrier of G2385R of LRRK2 was found in 7.7% of Parkinson's disease (PD) patients . There was no association between LRRK2 G2385R genotype and cognitive dysfunction assessed by MMSE Z score or MoCA in PD. The interaction terms between PD duration and the LRRK2 G2385R genotype were not significant for the MMSE Z score. There was an interaction between PD duration and LRRK2 G2385R genotype for cognitive decline assessed by MoCA score in PD. Abstract: Aside from the glucocerebrosidase gene, the genetic risk factors for cognitive decline in Parkinson's disease (PD) are controversial. We investigated whether the G2385R polymorphism in leucine-rich repeat kinase 2 gene ( LRRK2 ), a risk variant for the development of PD in East Asians, is associated with cognitive dysfunction in PD. We recruited 299 PD patients, consisting of 23 carriers and 276 non-carriers of LRRK2 G2385R, from 14 centers. Global cognitive function was assessed using the Mini-Mental State Examination (MMSE) or the Montreal Cognitive Assessment (MoCA). PD with cognitive dysfunction was defined as an MMSE Z score that, adjusting for age at study entry and years of education, was below -1.0 standard deviations. In multivariate analysis, PD duration, age at study entry and depression were significant risk factors for cognitive dysfunction as assessed by MMSE performance or the MoCA. In linear regression analysis of the association between MMSE Z scores and PD duration, there was no significant difference associated with the LRRK2 G2385R genotype. The interaction terms between PD duration and the LRRK2 G2385R genotype were not significant for the MMSE Z score but were significant for the MoCA. In conclusion, the LRRK2 G2385R genotype may not be associated with cognitive dysfunction in PD.